A time-sorting pitfall trap and temperature datalogger for the sampling of surface-active arthropods. (April 2017) - McMunn, Marshall S.
Graphical abstract: Abstract: Nearly all arthropods display consistent patterns of activity according to time of day. These patterns of activity often limit the extent of animal co-occurrence in space and time. Quantifying when particular species are active and how activity varies with environmental conditions is difficult without the use of automated devices due to the need for continuous monitoring. Time-sorting pitfall traps passively collect active arthropods into containers with known beginning and end sample times. The trap described here, similar to previous designs, sorts arthropods by the time they fall into the trap using a rotating circular rack of vials. This trap represents a reduction in size, cost, and time of construction, while increasing the number of time windows sampled. The addition of temperature data collection extends functionality, while the use of store-bought components and inclusion of customizable software make the trap easy to reproduce and use.